Implementasi Prinsip Demokrasi Pancasila dalam Membangun Karakter Anak di Panti Asuhan - Helga, Patricia; Kristy, Ellena; Grace, Viona; Silvana, Silvana; Lovela, Adelia; Tumanggor, Raja Oloan (Lembaga Yasin AlSys, 2024)
Pancasila democracy is a moral guideline that reflects the noble values of the nation that must be applied by every citizen to carry out aspects of life properly. Pancasila Democracy has an important effect on the welfare of national life. The implementation of Pancasila Democracy principles, especially the fourth principle emphasizes the importance of democratic decision-making through deliberation and consensus, which teaches children to respect opinions, be responsible, and work together to achieve common interests. Family is the first place for a child to build character. However, not all children get full support from their families. For some children who grow up in an orphanage environment, they view the orphanage as a facilitator in providing education and good role models. Therefore, foster parents have an important role in children's character education in orphanages. This study uses a qualitative approach with a literature study method by collecting literature sources related to the topic from journals, articles, and other information. The results of the study show that the principles of Pancasila democracy can be implemented by orphanage children by doing play activities, learning in groups, and learning to cooperate.